2017
DOI: 10.1080/14712598.2017.1296132
|View full text |Cite
|
Sign up to set email alerts
|

Immune and viral therapies for malignant primary brain tumors

Abstract: Glioblastoma multiforme (GBM) is a primary brain tumor with great lethality. Current standard of care with surgery, radiation therapy, and chemotherapy are ineffective in curing this disease. Recent advancements in biological therapies show promise in treating brain tumors. Areas covered: This article provides a review of: the peripheral activation of antigen presenting cells such as dendritic cells to stimulate T cells to recognize and destroy tumor cells within the brain; the ex vivo expansion and transfer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 149 publications
0
11
0
1
Order By: Relevance
“…18 Unfortunately, current therapies are not effective and cause important negative side effects. 1 Here we show for the first time that intrathecal ZIKV BR injections of 1 to 10 million virus particles in dogs represent a safe procedure since it did not trigger any negative clinical side effects in injected animals. More importantly, at autopsy, mature neurons from CNS regions showed no damage or any specific ZIKV BR -positive staining either.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…18 Unfortunately, current therapies are not effective and cause important negative side effects. 1 Here we show for the first time that intrathecal ZIKV BR injections of 1 to 10 million virus particles in dogs represent a safe procedure since it did not trigger any negative clinical side effects in injected animals. More importantly, at autopsy, mature neurons from CNS regions showed no damage or any specific ZIKV BR -positive staining either.…”
Section: Discussionmentioning
confidence: 66%
“…Despite aggressive current therapies, including surgery, radiation, and chemotherapy, the most common forms of adult and pediatric primary brain tumors remain lethal. 1 The treatment is not effective and sur-viving patients present important side effects that affect their quality of life. 2 Therefore, novel treatment options are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The initial ground truth label L(X, K) at K-th branch output is set to 1 if class K is the image-level label of X and to 0 otherwise. Take binary classification between class-1 (corresponds to 1th-branch) and class-2 (corresponds to 2th-branch ) as an example, the initial label vector for patches from class-1 WSI and class-2 WSI would be [1,0] and [0, 1] respectively and Non-Dis patches would be labelled as [0, 0] in the training process.…”
Section: Em-based Iterative Patch Labellingmentioning
confidence: 99%
“…In recent decades, brain tumors have become a serious health issue around the world [1]. In order to improve the survival rate of brain cancer, early and accurate diagnosis of brain cancer is essential.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, brain tumor has become one of the leading causes of death among children as well as in adults [1]. Some studies have showed that the number of people suffering and dying from brain tumor has increased to 300 per year during the last few decades [34].…”
Section: Introductionmentioning
confidence: 99%